Tax competitiveness as a significant factor in attracting foreign investment – the case of Serbia - Marjanović, Darko; Domazet, Ivana (Publishing House of Wroclaw University of Economics and Business, 2021)
Tax competitiveness signifies a strategy that the government uses to attract foreign investment through appropriate, privileged tax measures. It most commonly occurs between neighbouring countries, with significant tax reforms taking place in terms of the competitiveness of their tax systems. A high degree of a state’s competitiveness allows for a greater inflow of foreign investments, which, to a certain extent, can significantly affect its economic growth and development. Tax competition in itself means that one jurisdiction attempts to attract foreign capital by offering favourable tax treatment to foreign investors, most often through tax relief and tax exemptions, while at the same time reducing the tax base and/or tax rate. The main goal of this paper was to determine the degree of tax competitiveness of Serbia in relation to other European countries, classified both by region and globally. Based on the goals set, the authors conducted empirical research which allowed to reach the viewpoints of foreign investors in terms of tax competitiveness, based on their opinions and future expectations. The research involved the largest foreign investors who invested capital in Serbia in the past 20 years, and who carried out their business activities in other European countries or regions. The methodology of the research was based on a quantitative approach, allowing to obtain numerical data, their mutual comparability, and to determine the connection that exists between them. The results clearly indicate that the largest number of foreign investors believe that Serbia’s tax competitiveness is essentially the same compared to other European countries from the observed regions. These results can be of interest to fiscal policy makers, and it is very important that in the coming period there will be an increase in competitiveness, which can have positive effects both on the inflow of foreign investment and the economic growth and development of the country.
Argumenta Oeconomica, 2021, Nr 2 (47), s. 63-80
Keywords: tax competitiveness; economic growth and development; foreign investment